Financial Feasibility Of Aglaonema Commodity Ornamental Plant Business At Bibitbungaku Ornamental Plant Shop Tasikmalaya Regency - Nurzehan, Nida Nabila; Jakiyah, Ulpah; Fitriadi, Budhi Wahyu (Journal of Multidisciplinary Research, 2024)
Ornamental plants can be used as income for farmers and ornamental plants include businesses that are quite popular among the public. Aglaonema ornamental plants can be used as indoor decorations, this is due to the beauty possessed by this plant from the patterns and colors on its leaves. This study aims to analyze the financial feasibility of the Aglonema commodity ornamental plant business in Tasikmalaya Regency, especially at the Bibitbungaku Ornamental Plant Shop using the R/C Ratio. In this study only took 1 sample respondent, namely only the owner of Bibitbungaku Ornamental Plant Shop. Based on the results and discussion, it can be concluded in this study about the financial feasibility of the Aglaonema ornamental plant business, the R C Ratio value is 1.76 which indicates that the R/C Ratio value is more than one, so that from this analysis the Aglaonema ornamental plant business at the Bibitbungaku Ornamental Plant Shop is feasible to be developed further by considering increasing the knowledge and skills of farmers, as well as better environmental management.